DAMPAK PERUBAHAN PENGGUNAAN LAHAN BAGI PERTANIAN PERKOTAAN DI KAPANEWON KASIHAN - abraham, adam (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2022)
Urban agriculture faces big challenges from the availability of the space within the city and the high demand of lands for cluster houses. Such challanges brings negative impacts to urban agricultural lands. On the other hand, urban agriculture has great potential especially in providing food for the neighborhood and maintaining sustainability of the environment. This research aims to identify the impact of land use change that affects the urban agriculture farmer in urban area of Kasihan District. Deductive-qualitative approach is used in this research to give an explorative explanation of the phenomenon. According to the analysis, farmers perceive positive and negative impacts from the city development. The most perceived negative impacts are the land and water pollution, climbdown of productivity and isolation of the potential lands. In long term all those negative impacts could bring a risk of another spread of land use change phenomenon and environmental degradation.